ANALISIS PENGARUH EMPLOYEE ENGAGEMENT, KEPUASAN KERJA DAN STRESS KERJA TERHADAP KINERJA KARYAWAN PADA INDOMARET - Anang Triwahyono; Achmad Yani (Jurnal Ilmu Manajemen dan Akuntansi Terapan (JIMAT), 2021)
Indomaret is a minimarket network that provides basic needs and daily needs. In 1997 the company developed the first franchised outlet business in Indonesia, after having more than 230 stores. In 2015 there were 11,400 stores, 60% of which were self-owned and the rest were public property. Indomaret is spread evenly from Sumatra, Java, Madura, Bali, Lombok, Kalimantan and Sulawesi. The company motto is "Easy and Economical". Employee Performance As one of the results of work in terms of quality and quantity achieved by an employee in carrying out his duties. If the performance is below expectations, the customer will be disappointed or dissatisfied. Performance in line with expectations can make customers satisfied. In addition, performance that exceeds expectations can make customers very satisfied. The results prove that increasing employee engagement, job satisfaction, reducing work stress is expected to increase employee performance.